INTERACTIVE METHODS – AN IMPORTANT FACTOR TO INCREASE STUDENT CREATIVITY - Boqiyeva Marjona Shuhratovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The article discusses educational technologies for the development of the education system and increasing the participation of students in school mother tongue education. In the development of education, there is talk of increasing creativity, boosting students' ability to express themselves fully, and the effectiveness of using interactive teaching methods. Priority ideas were put forward during the lesson, such as organizing various games to increase student activity.